2022
DOI: 10.1186/s12864-022-08525-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of circRNA, miRNA, and mRNA profiles to reveal ceRNA regulation in chicken muscle development from the embryonic to post-hatching periods

Abstract: Background The growth and development of skeletal muscle are regulated by protein-coding genes and non-coding RNA. Circular RNA (circRNA) is a type of non-coding RNA involved in a variety of biological processes, especially in post-transcriptional regulation. To better understand the regulatory mechanism of circRNAs during the development of muscle in chicken, we performed RNA-seq with linear RNA depletion for chicken breast muscle in 12 (E 12) and17 (E 17) day embryos, and 1 (D 1), 14 (D 14), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…CircRNAs are characterized by abundant expression, stable structure, and evolutionary conservation. In this study, circRNAs from CEFs mainly originated from chromosomes 1, 2, and 3, consistent with the study by Lei et al on chicken muscle ( 22 ), Wang et al on hen granulosa cells ( 23 ), and Zhang et al on CEF and HD-11 cells ( 24 ). Our results showed that circRNAs from CEFs were mainly located in exons (80.8%), consistent with the findings of Wang et al and Chen et al, who studied circRNAs from hen granulosa and DF1 cells ( 13 , 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…CircRNAs are characterized by abundant expression, stable structure, and evolutionary conservation. In this study, circRNAs from CEFs mainly originated from chromosomes 1, 2, and 3, consistent with the study by Lei et al on chicken muscle ( 22 ), Wang et al on hen granulosa cells ( 23 ), and Zhang et al on CEF and HD-11 cells ( 24 ). Our results showed that circRNAs from CEFs were mainly located in exons (80.8%), consistent with the findings of Wang et al and Chen et al, who studied circRNAs from hen granulosa and DF1 cells ( 13 , 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…According to the main roles of lncRNA in the regulation of RNA at the epigenetic level, including the regulation of DNA methylation 56 , histone modification 57 and chromatin remodeling 58 , and at the transcriptional level, including the interaction with transcription factors 59 62 , proteins in the nucleus 63 and proteins in the cytoplasm 64 , and interaction with miRNAs 22 , 65 69 . Several studies have shown that the expression of some genes under AHS is modified 36 , 70 72 , possibly through the interaction with small or long noncoding RNAs 20 24 . Therefore, the identification of key coding genes and their corresponding regulatory elements (i.e., lncRNA and miRNA) is critically important to reveal the causative factors associated with AHS in liver of chickens, as liver is extremely vulnerable under the influence of heat stress 73 , 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous researches have reported multiple small and long non-coding RNAs that are crucially important for the resistance of chicken to HS via altering or regulating the expression levels of the protein coding genes 20 24 . lncRNAs are non-coding RNAs longer than 200 nucleotides, which can be divided into four categories including; intronic, intergenic, sense, and antisense lncRNAs 25 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they collectively regulate the expression levels of mRNA. The circRNA-miRNA-mRNA regulatory network is closely associated with various growth and development processes ( Lei et al, 2022 ; Xiao et al, 2022 ; Zou et al, 2020 ). circRNAs can act as ceRNAs ( Hansen et al, 2013 ) to regulate gene expression and thus control traits.…”
Section: Introductionmentioning
confidence: 99%